PEMBELAJARAN MODEL TEAM ASSISTED INDIVIDUALIZATION TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Andi Wijaya, Endah Rita S. Dewi, Veryliana Purnamasari (Universitas PGRI Yogyakarta, 2018)
The objective to be achieved in this research is to know the influence of learning model of assisted individualization team toward critical thinking ability and mathematics learningresult of class V SD Negeri Sawah Besar 02 Semarang. This research is quantitative researchin the form of True Experimental Design with Pretest-Posttest Control Group Design design.The study population is all students of grade V SD Negeri Sawah Besar 02 Semarangacademic year 2016/2017. Samples taken were 27 experiment class students and 27 controlclass students using non probability sampling technique. This research data is obtainedthrough test, documentation, and observation. Based on the results of the analysis of researchdata on the two tailed test critical thinking ability shows that t count > t table is 2.4514>2,0066 so Ho is rejected. The conclusion is that there is influence of learning model of teamassisted individualization toward critical mathematical thinking ability in class V SD NegeriSawah Besar 02 Semarang. Based on the results of the analysis of research data on two tail ttest the two learning outcomes show that t count > t table is 2.4514> 2,0066 so Ho is rejected.The conclusion is that there is influence of learning model of assisted individualization teamto the result of learning mathematics in class V SD Negeri Sawah Besar 02 Semarang. Basedon the results of this study suggestions that can be delivered is that the model of team assistedindividualized learning can be used as an alternative teacher in teaching.Keywords: Influence, Team Assisted Individualization Model.